Characterizing perimenstrual flares of hidradenitis suppurativa - Erin K. Collier, MPH; Kyla N. Price, BS; Tristan R. Grogan, MS; Haley B. Naik, MD, MHSc; Vivian Y. Shi, MD; Jennifer L. Hsiao, MD (Wolters Kluwer, 2020)
Background: Hidradenitis suppurativa (HS) predominantly affects women of childbearing age, and sex hormones are thought to play a role in HS pathogenesis. However, there is a paucity of data regarding the pattern of HS perimenstrual flares, as well as patient responses to hormone-based therapies. Objective: We aimed to characterize the temporal pattern of perimenstrual flares, as well as factors associated with perimenstrual flares. We also sought to investigate responses to hormonal therapies in women with HS. Methods: An anonymous web-based questionnaire was distributed to various online HS support groups in May 2020. Results: A total of 283 participants met the inclusion criteria as adult women who self-reported having HS and menstrual cycles. The majority (176 of 282 women; 62.4%) reported HS worsening with menses, and 86.9% (153 of 176 women) noted that perimenstrual HS flares occurred always or often. Most women (138 of 175 women; 78.9%) reported that their HS flared in the week preceding menses. Perimenstrual HS flares were more likely in women with a family history of HS compared with those without (49.6% vs. 28.2%; p = .019). More than a third of respondents who had been treated with spironolactone reported improvement of HS symptoms, but more than a quarter of participants who used medroxyprogesterone acetate or used a hormonal intrauterine device reported worsened HS symptoms. Conclusion: Female patients with HS have high rates of perimenstrual HS flares, specifically during the week preceding the onset of menses. Additional investigations on the role of sex hormones in HS pathogenesis and the efficacy of hormone-based therapies are warranted.